Exploring the Efficacy of Ketoconazole versus Ketoconazole Combined with Adapalene in Treating Pityriasis Versicolor: A Comparative Study: Ketoconazole versus Ketoconazole Adapalene in Pityriasis - Ahmad, Shafiq; Hussain, Shabir; Mustafa, Amjad; Feroz, Sumera; Zafar, Shafaq; Shaheen, Ghazala (Pakistan Journal of Health Sciences, 2024)
Pityriasis versicolor, a fungal infection causing skin discoloration, was commonly treated with antifungal agents like ketoconazole and adapalene, either alone or in combination. Objective: To compare the efficacy of ketoconazole alone versus the combination of ketoconazole and adapalene in the treatment of pityriasis versicolor. Methods: This study was conducted at Department of Pharmacology, Banu Medical College, Banu from May 2023 to October 2023. Total 90 (45 in each group) adult patients diagnosed with the condition were assigned to either treatment group. Group A was treated with ketoconazole 2% cream monotherapy, while Group-B was given combined therapy with ketoconazole 2% cream and adapalene 1% gel. Both groups underwent treatment for duration of four weeks, with instructions for application provided by the investigators. Treatment outcomes, including lesion clearance rates were evaluated at follow-up. The collected data underwent processing and analysis utilizing IBM SPSS, version 23.0. Results: Out of total participants 57 (63.3%) were male and 33 (36.7%) were females, with a mean age of 30.63 ± 8.38 years. Regarding lesion type, the distribution between hyperpigmented (51.1%) and hypopigmented (48.9%) lesions were relatively balanced. This study depicted a significantly higher proportion of patients in the combination therapy group (n=39, 86.7%) experienced improvement compared to those in the ketoconazole monotherapy group 21 (46.7%) (p < 0.001). Conclusions: In conclusion, this study demonstrates that the combination of ketoconazole and adapalene exhibits superior efficacy compared to ketoconazole alone in treating pityriasis versicolor.